A Practical Scheme to Improve Memorability of System-assigned Random Password - Meem, Fairuz Nawer; Noman, Rahat Al; Saha, Pritom; Pervez, Muhammad Shakil; Rahman, Ismat; Zaber, Moinul; Rumee, S T Ahmed (Dhaka University Journal of Applied Science and Engineering, 2023)
Most users follow common strategies and patterns while choosing passwords, which makes them easier to remember but often very weak in terms of security. System-assigned random passwords can be an answer to this problem. However, these random passwords are difficult to remember and hardly used by the users through their strong security guarantee. Recently researchers have been trying on devising techniques to remember random passwords. However, state-of-the-art methods have noticeable limitations such as - no upper case or special characters were considered, which is not practical for any good password. This paper proposes a novel scheme to aid users in remembering random passwords that do not suffer from these limitations. Users can select both graphical and text-based hints and associate them with systemassigned random passwords. Detailed user surveys were performed and the results showed that the proposed method can help users to remember random passwords with high accuracy. Using the proposed method, participants could recollect random passwords with an accuracy of 90.41% (average), which becomes 95% if case sensitivity is ignored. DUJASE Vol. 7(1) 29-37, 2022 (January)